Evaluation of Eggshell as Organic Fertilizer on Sweet Basil - V. T, Wijaya; S. S, Teo (International Journal of Sustainable Agricultural Research, 2019)
Food waste, for example, eggshell has been piling up on earth through the years. On the other hand, home-gardening has been a trend that encouraged by the government. The focus in this study is to decrease and use the eggshell waste by utilizing it as fertilizer. Eggshell has potential to become fertilizer for plants due to its nutrient content. The eggshell fertilizer used in this study was in liquid/foliar and solid form. The comparison of eggshell fertilizer and commercial fertilizer effectiveness was conducted to see their compatibility in basil’s growth. The chemical analysis was conducted on eggshell tea fertilizer to see the nutrient content. The result from this study shows that eggshell fertilizer in liquid/foliar form is compatible with commercial fertilizer. The compatibility might be achieved due to nutrients, such as nitrogen, potassium and chloride in eggshell tea fertilizer. However, the eggshell fertilizer in liquid form performed better than in its solid form. Further studies could be focusing on the effectiveness of crushed eggshell fertilizer in a more controlled environment. In conclusion, eggshell fertilizer can be used as an alternative for fertilizer in home-gardening due to its compatibility to commercial fertilizer. The result of this study might contribute to reducing food waste, specifically eggshell waste. The result of this study might lead to more utilization of eggshell waste, especially as fertilizer, thus decrease the cost of using commercial fertilizer.